Estimating excess visual loss from neovascular age-related macular degeneration in the UK during the COVID-19 pandemic: a retrospective clinical audit and simulation model. Issue 4 (15th April 2022) - Thomas, Darren S; Warwick, Alasdair; Olvera-Barrios, Abraham; Egan, Catherine; Schwartz, Roy; Patra, Sudeshna; Eleftheriadis, Haralabos; Khawaja, Anthony; Lotery, Andrew; Muller, Philipp L; Hamilton, Robin; Preston, Ella; et al.
Abstract : Objectives: To report the reduction in new neovascular age-related macular degeneration (nAMD) referrals during the COVID-19 pandemic and estimate the impact of delayed treatment on visual outcomes at 1 year. Design: Retrospective clinical audit and simulation model. Setting: Multiple UK National Health Service (NHS) ophthalmology centres. Participants: Data on the reduction in new nAMD referrals were obtained from four NHS Trusts comparing April 2020 with April 2019. To estimate the potential impact on 1-year visual outcomes, a stratified bootstrap simulation model was developed drawing on an electronic medical records dataset of 20 825 nAMD eyes from 27 NHS Trusts. Main outcome measures: Simulated mean visual acuity and proportions of eyes with vision ≤6/60, ≤6/24 and ≥6/12 at 1 year under four hypothetical scenarios: 0-month, 3-month, 6-month and 9-month treatment delays. Estimated additional number of eyes with vision ≤6/60 at 1 year nationally. Results: The number of nAMD referrals dropped on average by 72% (range 65%–87%). Simulated 1-year visual outcomes for 1000 nAMD eyes with a 3-month treatment delay suggested an increase in the proportion of eyes with vision ≤6/60 from 15.5% (13.2%–17.9%) to 23.3% (20.7%–25.9%), and a decrease in the proportion of eyes with vision ≥6/12 (driving vision) from 35.1% (32.1%–38.1%) to 26.4% (23.8%–29.2%). Outcomes worsened incrementally with longer modelled delays. Assuming nAMD referrals are reduced to this level for 1 month nationally, these simulated results suggest an additional 186–365 eyes with vision ≤6/60 at 1 year. Conclusions: We report a large decrease in nAMD referrals during the COVID-19 lockdown and provide an important public health message regarding the risk of delayed treatment. As a conservative estimate, a treatment delay of 3 months could lead to a >50% relative increase in the number of eyes with vision ≤6/60 and 25% relative decrease in the number of eyes with driving vision at 1 year.